DECISION SUPPORT SYSTEM FOR CAMPING GROUND TOURISM DESTINATION SELECTION IN KUNINGAN USING TOPSIS METHOD - Rafiq, Luthfi Khairul; Novianti, Dian; Deni, Deni (Program Studi Teknik Informatika Universitas Muhammadiyah Cirebon, 2025)
There are several interesting camping sites in Kuningan. However, this variation often makes it difficult for tourists to choose the most suitable camping site for their needs and tastes. Decision support systems (DSS) are needed in the digital era and advances in information technology to help tourists choose the ideal travel location. TOPSIS (Technique for Order Preferences by Similarity to Ideal Solutions) is one of the useful decision-making techniques. Using this technique, options are ranked according to how close they are to the positive and negative ideal solutions. This allows them to offer transparent and impartial suggestions for each camping destination based on various factors. The objectives of this study are: (1) Develop and build a Decision Support System (DSS) that can facilitate the process of selecting camping destinations in Kuningan; and (2) Utilize the TOPSIS approach to calculate and prioritize the proposed camping locations. The waterfall method of system development is used in this qualitative study with a descriptive analysis methodology. In this study, literature review, interviews, and observations are the methods used to collect data. Keywords: Decision Support System, Kuningan Camping Tourism, Topsis